Nutrient digestibility of fishmeal rations in primates - N. V. Gaponov; L. N. Gamko (Ветеринария сегодня)
The results of the study on effects of fishmeal on nutrient digestibility and intake in primates are given in the paper. Fishmeal is a feeding stuff, manufactured from fish, marine mammals, invertebrates not suitable for human consumption and by-products of their processing. Fishmeal nutrient composition includes natural substances and minerals, including phosphorus, calcium, iodine, selenium, several essential amino acids, as well as vitamins А, D and В complex. Fishmeal is known to be rich in digestible energy and proteins. One kilogram of fishmeal contains 700 grams of raw protein and up to 15 MJ of digestible energy. It should be noted that fishmeal is easily digested by animals. Nevertheless, there is a lack of data in publications on use of fishmeal as high protein feed in rations of primates. In this regard, the aim of the study was to analyze the effects of fishmeal on digestibility of mixed feed nutrients in male rhesus-macaques and to use the obtained results for understanding of prospects of fishmeal further use for feeding primates. The chemical composition and nutritional value of the total mixed ration was determined. The economic effectiveness of the fishmeal use in the rations of primates was calculated. Based on the experimental data, it was established that the inclusion of fishmeal (18% out of total) into the diet contributes to the improvement of feed intake in experimental primates and reduces the costs of complete granular feed.